Metal–organic frameworks with aggregation‐induced emission - Hang Xu; Peng Cheng (Aggregate, 2024)
Abstract Aggregation‐induced emission (AIE) materials exhibit remarkable emission in the aggregated or solid state while demonstrating minimal emission in dilute solutions. In contrast to conventional luminescent materials, AIE luminogens (AIEgens) offer several advantages in the aggregate state, including high quantum yield, excellent photostability, and low background signals, making them highly promising for diverse applications. Integrating AIEgens into designable metal–organic frameworks (MOFs) enables tunable and well‐ordered AIE materials, allowing for precise control over photophysical properties and deeper exploration of AIE mechanisms. Numerous AIE MOFs have been constructed and investigated, and several reviews focus on their structure design and applications in sensing and bioimaging. This review highlights the state‐of‐the‐art advancements in AIE MOFs, including mechanisms, design strategies, and applications in chemical sensing, bioimaging, and disease therapy. The challenges associated with practical applications of AIE MOFs are also addressed, with an emphasis on their large‐scale production involved interdisciplinary collaboration. This comprehensive review aims at guiding further development of AIE MOFs and promoting their practical applications in analysis, healthcare, and other luminescence related fields.